Corporate Social Responsibility in Family-Owned SMEs: Examining Influential Factors Through the SGE21 Standard - Ríos-Manríquez, Martha (European Journal of Family Business, 2025)
This study investigates the influence of the factors established by the SGE21 standard in family businesses in a Latin American country, specifically Mexico. Corporate social responsibility (CSR) is a critical issue for companies, which increasingly adopt social responsibility models for ethical, philanthropic, stakeholder-driven, or competitive reasons. However, few studies focus on small and medium-sized family businesses (family SMEs) in this context. This research has two main objectives. First, it seeks to determine whether factors such as corporate governance, customers, suppliers, employees, the social and natural environment, investors, competition, public administration, and company age influence the CSR practices of family SMEs. Second, it assesses the level of CSR adoption in these businesses according to the Ethical and Socially Responsible Management System (SGE21 standard). The study analyzes data from 65 family businesses applying four types of analysis: exploratory factor, descriptive, correlational, and linear regression, employing the Ordinary Least Squares (OLS) method. The results indicate that most family businesses exhibit an intermediate level of adoption of the t SGE21 standard indicators. The key factors influencing CSR in family SMEs are corporate governance, suppliers, employees, and the social-natural environment. This research contributes to the existing literature by providing insights into CSR from the perspective of Latin American family businesses. It highlights that, even without prior knowledge of the variables and indicators established by the SGE21 standard, these businesses actively engage with CSR indicators due to their inherent commitment to social responsibility. Furthermore, the findings underscore the adaptability of the SGE21 standard for implementation in Latin America.